A COMPARATIVE CLINICAL STUDY ON THE EFFICACY OF SUKUMARAGRITHA IN SUKHAPRASAVA - Jadhav, Sarang; Padmasaritha, K; Siddesh, Sunita; Mishra, B. (International Journal of Ayurveda and Pharma Research, 2015)
Antenatal care is essential to maintain the health in the affluent society and to improve the health in developing countries. Ensuring healthy and safe motherhood with utmost care rendered to every woman is the outright responsibility of an obstetrician. Child birth is a very dynamic process and the women need to be well prepared for it. The contemporary system uses analgesia and anaesthesia to reduce pain during labour but have no proved measures to shorten the period of 1st stage of labour. In Ayurveda similar efforts are being incorporated by means of drugs, among them there are many formulations for the pregnant women to deliver with ease. Sukumara Gritha which is used to correct Vata dosha has been selected for the present study. A comparative clinical study with pre test and post test design conducted on 40 pregnant women fulfilling the inclusion criteria were selected randomly from OPD and IPD of Prasooti Tantra Evam Stree Roga Department of Shri Kalabyreshwaraswamy Ayurvedic Medical College Hospital and Research Center, Bangalore and assigned into two groups, each comprising of 20 patients. Group A 20 patients were administered with Sukumara Gritha 2 tsf before food with luke warm water for 1 month before EDD. Group B 20 patients were administered with Goghrita. Continuous observation was done for the progress of labour using Partogram and Bishops score. Results were calculated and statistically and showed significant in1st stage of labour. For second and third stage, no difference was found. Group A showed better cervical ripening and shortened the number of hours in the first stage of labour compared to Group B.